Development and evaluation of a non-electronic Sepedi graphic symbol-based AAC system for use with preliterate children - Tonsing, Kerstin Monika (University of Pretoria, 2025)
Thesis (PhD (Augmentative and Alternative Communication))--University of Pretoria, 2025.